ANALISI FRAMING PEMBERITAAN SIDANG KASUS KOPI SIANIDA JESSICA KUMALA WONGSO DI MEDIA ONLINE WWW.KOMPAS.COM - Tilawati Rosel; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The news of the murder of Wayan Mirna Salihin became the news, early in 2016 that colored the mass media in ndoneisa. The investigation team also named Jessica Kumala Wongso as a sole suspect, from previously only a witness status. One of media that gives great attetion to this case is online media kompas.com. this research was conduted to see how kompas.com contruct the news of Jessica’s trial and how the ideology’s media in the news. This research arms to determine the construction of news and media ideology in the news coverage conducted kompas.com on the rubric “Mystery Mirna’s murder” from August 15th – October 27th 2016.This research uses qualitative method with data collection is documentation, interview, and literature study. The subject of this research is the trial contained in the rubric of the “Mystery Mirna’s Murder” from August 15th – October 27th 2016, with the analysis units of 11 articles seleted in four categories : the prosecution witness, Jessica’s witness, Jessica’s testimony and the final decision of the panel of judges. Data were analyzed using Robert N. Entman’s framing analysis tool.The result of this research found that the construction of the news conducted by using framing Entman’s model, that can be know the element of define problem of kompas.com emphasize the linkage of Jessica on the death of Mirna. The element of diagnose cause and make moral judgment kompas.com showed how the evidence, arguments of the experts and judges believe jessica has the oppurtunity to put cyanide into the Mirna’s coffee. The last element is treatment reccomendation, kompas.com is not straightforward in reporting the from of problem solving and also offen does not include treatment reccomendation in the news. Kompas.com also tends to priorituze economic’s of the raising the issue of Jessica’s crime track record to increase advertising revenue from the news of this cyanide coffee’s case and set a side their own ideology that is independent, fair and prosperous.